Faktor-Faktor Yang Mempengaruhi Nilai Perusahaan (Studi Empiris: Industri Consumer Goods) - Yunike Berry; Nurhalizha Fadhilah (Jurnal Bisnis dan Ekonomi, 2022)
The purpose of this study was to determine the factors that affect firm value. The variables used in this study are dividend policy, investment decisions, managerial ownership, profitability, leverage, firm size and firm value. The research method uses quantitative research methods. Sources of data in this study using secondary data obtained from the official website of the Indonesia Stock Exchange with a sampling technique using the Purposive Sampling method. The population used in this study were all companies in the Consumer Goods Industry sector listed on the Indonesia Stock Exchange during the research period from 2016-2019 as many as 59 companies with a total sample of 16 companies. The data analysis method uses panel data regression model. The results show that dividend policy, investment decisions, managerial ownership have no significant effect on firm value, while profitability, leverage and firm size have an effect on firm value.